2021
DOI: 10.1021/acsami.1c09034
|View full text |Cite
|
Sign up to set email alerts
|

Improved Biocompatible, Flexible Mesh Composites for Implant Applications via Hydroxyapatite Coating with Potential for 3-Dimensional Extracellular Matrix Network and Bone Regeneration

Abstract: Hydroxyapatite (HA)-coated metals are biocompatible composites, which have potential for various applications for bone replacement and regeneration in the human body. In this study, we proposed the design of biocompatible, flexible composite implants by using a metal mesh as substrate and HA coating as bone regenerative stimulant derived from a simple sol–gel method. Experiments were performed to understand the effect of coating method (dip-coating and drop casting), substrate material (titanium and stainless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…Those results confirm similar nanostructure to the one obtained for HA powders dried at higher temperature (700°C). 35
Figure 3.Representative HR-TEM images for HA coating powders (scratched off from substrates’ surface) dried at various temperatures: (a, b) 90°C (red arrow in a indicates nanorod length), (c, d) 150°C (red arrow in c indicates nanorod length). Pure HA plane spaces of d = 0.81 nm (001), d = 0.34 nm (002), and d = 0.31 nm (102) are marked in panels b and d. Scale bar is 50 nm for (a, c) and 20 nm for (b, d).
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Those results confirm similar nanostructure to the one obtained for HA powders dried at higher temperature (700°C). 35
Figure 3.Representative HR-TEM images for HA coating powders (scratched off from substrates’ surface) dried at various temperatures: (a, b) 90°C (red arrow in a indicates nanorod length), (c, d) 150°C (red arrow in c indicates nanorod length). Pure HA plane spaces of d = 0.81 nm (001), d = 0.34 nm (002), and d = 0.31 nm (102) are marked in panels b and d. Scale bar is 50 nm for (a, c) and 20 nm for (b, d).
…”
Section: Resultsmentioning
confidence: 99%
“…For instance, previous work on flexible, HA-coated metallic meshes showed that mesh size (i.e., open areas) had an effect on extracellular matrix development. 35 Therefore, PEEK meshes and cellulose mats should be considered for future biocompatibility studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations